3D‐Printed Breast Prosthesis that Smartly Senses and Targets Breast Cancer Relapse - Lu Wang; Chenyang Ye; Xiangjie Xue; Mingjun Xie; Yicheng Zhi; Xiao Feng; Pengcheng Zhao; Jichun Zhou; Mi Mi; Jinrui Li; Qinhao Gu; Ye Zhao; et al. (Advanced Science)
Abstract Breast reconstruction is essential for improving the appearance of patients after cancer surgery. Traditional breast prostheses are not appropriate for those undergoing partial resections and cannot detect and treat locoregional recurrence. Personalized shape prostheses that can smartly sense tumor relapse and deliver therapeutics are needed. A 3D‐printed prosthesis that contains a therapeutic hydrogel is developed. The hydrogel, which is fabricated by crosslinking the polyvinyl alcohol with N1‐(4‐boronobenzyl)‐N3‐(4‐boronophenyl)‐N1, N1, N3, N3‐tetramethylpropane‐1,3‐diaminium, is responsive to reactive oxygen species (ROS) in the tumor microenvironment. Specifically, RSL3, a ferroptosis inducer that is loaded in hydrogels, can trigger tumor ferroptosis. Intriguingly, RSL3 encapsulated in the ROS‐responsive hydrogel exerts antitumor effects by increasing the numbers of tumor‐infiltrated CD4+ T cells, CD8+ T cells, and M1 macrophages while reducing the number of M2 macrophages. Therefore, this new prosthesis not only allows personalized shape reconstruction, but also detects and inhibits tumor recurrence. This combination of aesthetic appearance and therapeutic function can be very beneficial for breast cancer patients undergoing surgery.